Analyzing the difference in image quality between different ghost imaging systems using a unified optical transfer function. (12th May 2021) - Luo, Bin; Bai, Yanfeng; Fu, Xiquan
Abstract: The optical transfer function (OTF), which correspond to the frequency domain, is of fundamental importance in characterizing imaging ability in optical imaging systems. By using the Collins formula and the optical transfer matrix theory, a simple and unified analytical expression of OTF is presented in any ghost imaging (GI) system. By comparing the spectrum distribution of OTF between different GI systems, one can predict which imaging system can provide better imaging quality when the same imaging object is used. Theoretical and experimental results are also implemented to verify our results.